2009
DOI: 10.1002/anie.200904671
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dehydrative Cyclization of ω‐Hydroxy Allyl Alcohols Catalyzed by Ruthenium Complexes

Abstract: Chiral cyclic ethers constitute one of the most important structural units in biologically active compounds such as polycyclic ethers, polyether antibiotics, acetogenins, as well as coumaran-and chromane-related natural products.[1] Among many key building blocks reported so far, a-alkenyl-substituted cyclic ethers are widely recognized as the most useful because the alkenyl moiety can be transformed into a wide range of functionalities, thereby facilitating further elongation. The development of an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Cyclization using 2j with a C(3)-methyl substituent afforded 3j with a 9:1 C(2)/C(5) regioselectivity and in a 78% total yield (Table , entry 17). Elongation of the methylene tether from three to four carbons gave a pyrrole-fused vinylazepane 3k with er = 97:3, whereas shortening from three carbons to two carbons led to no production of the desired dihydropyrrolidine 3l (Table , entries 18 and 19), in contrast to the corresponding OH case . Replacement of the pyrrole of 2a with indole resulted in no reaction.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Cyclization using 2j with a C(3)-methyl substituent afforded 3j with a 9:1 C(2)/C(5) regioselectivity and in a 78% total yield (Table , entry 17). Elongation of the methylene tether from three to four carbons gave a pyrrole-fused vinylazepane 3k with er = 97:3, whereas shortening from three carbons to two carbons led to no production of the desired dihydropyrrolidine 3l (Table , entries 18 and 19), in contrast to the corresponding OH case . Replacement of the pyrrole of 2a with indole resulted in no reaction.…”
supporting
confidence: 68%
“…We have challenged the unachieved issue using our catalyst, ( R )- 1 , shown in Figure a. The CpRu/Brønsted acid hybrid complex, which is in a quick equilibrium between ( R , R Ru )- 1 and ( R , S Ru )- 1 , efficiently catalyzes the dehydrative intramolecular asymmetric allylation of protic nucleophiles (NuH) such as OH, COOH, NHAc, and NHTs, and to selectively furnish various exo-trig cyclic ethers, lactones, and saturated N-heterocycles with up to a >99:1 S / R enantiomeric ratio (er). A detailed study on the mechanism using a substrate with OH as the terminal NuH strongly supported that the major S enantiomer should be produced via a σ-allyl Ru intermediate .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5, the Intramol RDACat, [Ru(II) Cp(CH 3 CN) 3 ]PF 6 /(R)-3 ((R)-4), quantitatively cyclizes an aliphatic allylic alcohol, (E)-hept-2-ene-1,7-diol (5 a), to obtain 2-vinyltetrahydro-2H-pyran (6 a) with an S/R er of 97 : 3 with 6-exo-trig selectivity ([substrate] = 100-1000 mM; 0.1 mol% of (R)-4; N,N-dimethylacetamide (DMA); 100 °C; 1-3 h). [15] Aprotic solvents such as N,N-dimethylformamide (DMF), tetrahydrofuran (THF), and cyclopentyl methyl ether were adopted. Protic solvents such as tert-butyl alcohol (t-BuOH) and isopropyl alcohol may also be used although the er is marginally decreased.…”
Section: Alcohol Allylationmentioning
confidence: 99%
“…The scope of the reaction revealed that in almost all of the cases the cyclic products 10 were obtained with high yields (up to 99%) and excellent selectivities (up to 98% ee). Interestingly, the catalytic system and its analogs were first developed ten years ago by Kitamura et al and have been used in similar asymmetric intramolecular dehydrative allylations ( Figure 6C; Tanaka et al, 2009;Seki et al, 2012;Suzuki et al, 2015). In the initial publication, the chloro group seemed to play a more crucial role than just a steric control unit and it was speculated that the chloro group helped to stabilize the TS by lowering the LUMO level (Tanaka et al, 2009).…”
Section: Xbs In Enhancing Reactivitymentioning
confidence: 99%